Cooperative, Connected and Automated Mobility Service Continuity in a Cross-Border Multi-Access Edge Computing Federation Scenario - Hosseini, Seyed M.; Jooriah, Mohannad; Rocha, David; Almeida, João; Bartolomeu, Paulo; Ferreira, Joaquim; Rosales, Carlos; Miranda, Marta (Frontiers in Future Transportation, 2022)
The paradigm shift in transportation systems towards Cooperative, Connected, and Automated Mobility (CCAM) aims to improve vehicle maneuverability, reduce pollution, and increase safety. CCAM is primarily responsible for ensuring the best mobility environment, making it one of the major trends in the automotive industry. However, taking advantage of CCAM in Cross-Border Corridors (CBC) is challenging, where it goes beyond infrastructure deployment costs, and all of which are related to supporting Service Continuity (SC) for mobile users, especially in light of the diversity of territories, network coverage areas, international roaming agreements and type of cooperative maneuvers. As a solution to this challenges, the paper proposes and implements a new architecture for CCAM SC in CBCs that combines a federation of Multi-access Edge Computing (MEC) concepts to maintain SC.